Immunotherapy in advanced, G12C-mutant non-small-cell lung cancer: current strategies and future directions - Nadia Ghazali; Marina C. Garassino; Natasha B. Leighl; Christine M. Bestvina (Therapeutic Advances in Medical Oncology)
Kirsten rat sarcoma ( KRAS ) mutations are present in up to 25% of non-small-cell lung cancer (NSCLC). KRAS G12C is the most common type of mutation, representing approximately half of the cases in KRAS -mutant NSCLC. Mutations in KRAS activate the RAF-MEK-ERK pathway, leading to increased cell proliferation and survival. Recent advances in drug development have led to the approval of KRAS G12C inhibitors sotorasib and adagrasib. This review explores the emerging therapeutic strategies in KRAS G12C-mutant NSCLC, including dual checkpoint blockade and combinations with checkpoint inhibitors, with a focus on the setting of advanced disease.